2022
DOI: 10.3389/fpls.2022.1014236
|View full text |Cite
|
Sign up to set email alerts
|

The tobacco chloroplast YCF4 gene is essential for transcriptional gene regulation and plants photoautotrophic growth

Abstract: A tobacco chloroplast hypothetical open reading frame 4 (YCF4) has been reported as a non-essential assembly factor for photosynthesis based on an incomplete knockout of YCF4, just 93 of 184 amino acids from the N-terminus were knocked out. On the other hand, we removed the complete sequence of YCF4 from tobacco chloroplasts and observed that ΔYCF4 plants were unable to survive photoautotrophically as their growth was hampered in the absence of an external carbon supply, clearly showing that the YCF4 is essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In particular, the seven genes ( clpP , rps7 , rps12 , rps14 , rps16 , rps19 , and ycf2 ) are only found to have signals of positive selection in the Ceratocephala plastome, implying that these seven genes might have been associated with the adaptation of Ceratocephala to arid environments. Zhong et al [ 36 ] also found that the ycf2 was gene under positive selection in Helianthus tuberosus (Asteraceae), which grows in saline, alkaline and dry conditions as a widely cultivated plant in Northwest China. The two genes ( rpl32 and ycf4 ) are only found to have signals of positive selection in the Myosurus plastome, implying that they might have been associated with the adaptation of Myosurus to aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the seven genes ( clpP , rps7 , rps12 , rps14 , rps16 , rps19 , and ycf2 ) are only found to have signals of positive selection in the Ceratocephala plastome, implying that these seven genes might have been associated with the adaptation of Ceratocephala to arid environments. Zhong et al [ 36 ] also found that the ycf2 was gene under positive selection in Helianthus tuberosus (Asteraceae), which grows in saline, alkaline and dry conditions as a widely cultivated plant in Northwest China. The two genes ( rpl32 and ycf4 ) are only found to have signals of positive selection in the Myosurus plastome, implying that they might have been associated with the adaptation of Myosurus to aquatic environments.…”
Section: Discussionmentioning
confidence: 99%
“…The ycf4 gene has been described as a highly conserved protein in plants, green algae, and cyanobacteria. Recently, a study on Nicotiana tabacum showed that the chloroplast ycf4 gene is essential for transcriptional gene regulation and plant photoautotrophic growth [52]. Positive selection signatures in ycf4 and clpP show that these genes may have played important roles in the speciation of Ribes species and their adaptation to diverse environments.…”
Section: Discussionmentioning
confidence: 99%
“…A collection of genes called hypothetical chloroplast open reading frames (ycfs) is still unknown to have all of its specialized roles fully understood. Some of these ycfs have been classified as non-essential, while others have been classified as essential elements [5].…”
Section: Advances In Chloroplast Genomicsmentioning
confidence: 99%